Utility of the Modified Surgical Apgar Score in a Head and Neck Cancer Population. (13th February 2018) - Day, Kristine E.; Prince, Andrew C.; Lin, Chee Paul; Greene, Benjamin J.; Carroll, William R.
Abstract : Objective: The Surgical Apgar Score (SAS) is a validated postoperative complication prediction model. The purpose of this study was to investigate the utility of the SAS in a diverse head and neck cancer population and to compare it with a recently developed modified SAS (mSAS) that accounts for intraoperative transfusion. Study Design: Case series with chart review. Setting: Academic tertiary care medical center. Subjects and Methods: This study comprised 713 patients undergoing surgery for head and neck cancer from April 2012 to March 2015. SAS values were calculated according to intraoperative data obtained from anesthesia records. The mSAS was computed by assigning an estimated blood loss score of zero for patients receiving intraoperative transfusions. Primary outcome was 30‐day postoperative morbidity. Results: Mean SAS and mSAS were 6.3 ± 1.5 and 6.2 ± 1.7, respectively. SAS and mSAS were significantly associated with 30‐day postoperative morbidity, length of stay, operative time, American Society of Anesthesiologists status, race, and body mass index ( P <. 05); however, no significant association was detected for age, sex, and smoking status. Multivariable analysis identified SAS and mSAS as independent predictors of postoperative morbidity, with the mSAS ( P =. 03) being a more robust predictor than the SAS ( P =. 15). Strong inverse relationships were demonstrated for the SAS and mSAS with length of stay and operative time ( P <. 0001). Conclusion: The SAS serves as a useful metric for risk stratification of patients with head and neck cancer. With the inclusion of intraoperative transfusion, the mSAS demonstrates superior utility in predicting those at risk for postoperative complications.